Effects of Home Language Environment and Household Crowding on Early Expressive Language Development. Issue 4 (May 2020) - San San Kyaw, Khin; Tin Tin, Sandar; Underwood, Lisa; Grant, Cameron
ABSTRACT: Objective: This study examined prospective associations of the home language environment (HLE) and household crowding with expressive language development in 2-year-old children using the data from the Growing Up in New Zealand study, a population-based prospective cohort study. Methods: A total of 5960 children were included. The HLE (playing games, talking in everyday activities, playing with toys, singing songs, and reading books) and household crowding were measured when the children were 9 months old. Language development was assessed using the MacArthur-Bates Communicative Development Inventories (CDIs)—II short form (A) at age 2 years. Maternal and child characteristics were measured antenatally and when the children were 9 months old. Results: Each HLE activity was associated with higher language scores. A high HLE score, defined as doing at least 3 of the 5 HLE activities at least once daily, was associated with an increase in the language score of 6.31 units (95% confidence interval [CI] 5.00 to 7.62, p < 0.0001). The effect of the HLE was less pronounced in more crowded homes (coefficient = −2.24, 95% CI −0.47 to 4.97, p = 0.106) compared with less crowded homes with at least one other child (coefficient = 6.19, 95% CI 4.28 to 8.10, p < 0.0001) or with no other children (coefficient = 8.19, 95% CI 5.69 to 10.70, p < 0.0001). Conclusion: These findings underscore the need to consider various aspects of the home environment in future interventions aiming to facilitate language development in young children.